2020
DOI: 10.1111/ijlh.13436
|View full text |Cite
|
Sign up to set email alerts
|

Blast size‐specific flowcytometric ploidy assessment using FxCycleTM Violet dye and its correlation with conventional cytogenetic ploidy in pediatric precursor B‐lineage acute lymphoblastic leukemia patients

Abstract: Introduction Numerical chromosomal abnormalities (aneuploidies), present in approximately 30%‐50% of pediatric precursor B‐lineage acute lymphoblastic leukemia (B‐ALL) patients, are commonly identified through a laborious conventional cytogenetic (CG) technique. Flow cytometry (FCM) can identify both physical and fluorescent properties of cells together, and by using fluorescent nucleic‐acid‐binding dyes, FCM can identify variations in total nucleic‐acid content of cells. FxCycleTM Violet dye (FxCV) is a selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…[21] Hypodiploid MM by DNA content flow cytometry is rarer, occurring in <2% of newly diagnosed MM patients; the previous studies have shown these patients to be unresponsive to therapy and to have short survival. [13,20] In recent studies, flow cytometric ploidy analysis is increasingly being used in the analysis of B-ALL with its correlation of cytogenetic-based ploidy stratification and risk assessment, [22] and other studies are being done to assess the potential role in the detection of measurable residual disease. [23] In summary, this is the first study from our center on ploidy analysis using flow cytometry which helped us in standardizing the method.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Hypodiploid MM by DNA content flow cytometry is rarer, occurring in <2% of newly diagnosed MM patients; the previous studies have shown these patients to be unresponsive to therapy and to have short survival. [13,20] In recent studies, flow cytometric ploidy analysis is increasingly being used in the analysis of B-ALL with its correlation of cytogenetic-based ploidy stratification and risk assessment, [22] and other studies are being done to assess the potential role in the detection of measurable residual disease. [23] In summary, this is the first study from our center on ploidy analysis using flow cytometry which helped us in standardizing the method.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry-based cell cycle detection (iCCD) 53,54 • Geminin: Highest expression in S/G2/M phase and degrades after M phase • Chromatin licensing and DNA replication factor 1 (Cdt1): Highest expression in G1 phase and degrades before S phase • Gamma H2A.X: Marker for DNA double-strand breaks (DSBs) 55 Fluorescence in situ hybridization (FISH) 56 • Ploidy assessment by centromere and α-satellite DNA assessment probes Fluorescent ubiquitination-based cell cycle indicator (FUCCI) 57 • Fluorescence-labelled proteins tagged with Cdt 1 and Geminin • Time-lapse photographs are used to identify both temporality and spatial organization of cells in culture according to their stage in cell cycle Radioisotope-labeled DNA 58 • Incorporating radioisotope (now replaced by nucleoside analogues) into the DNA to calculate the time spent by a cell across the cell cycle stages Flow cytometry 2,3,8,9,52 Univariate • Using DNA binding dyes that enable only cellular DNA content assessment • Applicable in samples that have only/predominantly tumor cells…”
Section: Technique Brief Descriptionmentioning
confidence: 99%
“…However, ploidy evaluation by FCM is not sensitive in assessing aneuploidies involving smaller chromosomes. 9 Role of DNA Index in B-Lineage Acute Lymphoblastic Leukemias Hyperdiploidy (51-65 chromosomes) is observed in nearly 30% of pediatric patients diagnosed with B-ALL and is associated with a favorable prognosis. [14][15][16] These hyperdiploid blasts are highly susceptible to apoptosis and hence require stringent conditions for their ex vivo survival.…”
Section: Dna Indexmentioning
confidence: 99%
See 2 more Smart Citations